EFL Learners’ Cultural Perspectives towards Online Learning through Flipped Classrooms in Indonesia for Facing 4.0 Industry Era - Mulyanto Mulyanto; Ahmad Heki Sujiatmoko (Journal of Social Science, 2022)
The current study was aimed to investigate the cultural perspectives on online learning through the flipped learning activity to face the 4.0 industry era in Indonesia. Online learning has been a trend in education as the development of education in the world refers to the current situations due to the development of technology. The important thing needed to be considered is concerned with the strategy of providing the learning time allocation and using technology. The best alternative strategy to support online learning is conducting the flipped learning activity. However, it is not an easy matter since some cultural aspects in Indonesia can be great obstacles. That's why it is crucial to recognize the problems and find the solutions referring to the existing cultural dimensions. The results revealed that the way how the learners studied English through the online learning activities was mostly influenced by the cultural dimensions such as getting passive in the class, focusing on getting good grades, expecting the teachers’ dominations in the class, and getting fond of being given playful learning activities. Regarding this, some solutive efforts were also done by the teachers in the form of flipped learning activities leading the acts of building the classroom interactions through questioning and giving various tasks targetting to improve the generic capabilities. Hence, it is recommended that both the EFL teachers and learners can overcome the problems related to the existence and influence of the cultural dimensions by implementing the flipped learning activities to support the online learning activities conducted for reaching better academic achievements through the developments of their generic capabilities to face the 4.0 industry era.